Gavaksha motif - Temples of India Project Team (Jio Institute, 2024)
Broken debris from the original temple assembled on the landing of the first set of steps on the adhisthana. The split gavaksha motif is repeated all through the temple. It is a motif that is often seen in Hindu temples.